Properties of the FM: Series with Zero Convergence RADII - Arteca, Gustavo Alberto (1990)
This section starts the analysis of models with power series expansions with zero convergence radius. Our first aim is to apply the formalism developed in §.44 to a simple model with the above features and to determine the conditions under which the FM leads to a convergent sequence.